Formulation and evaluation of niosomes-based chlorpheniramine gel for the treatment of mild to moderate skin allergy. Issue 1 (31st December 2022) - Afreen, Urooj; Fahelelbom, Khairi Mustafa; Shah, Syed Nisar Hussain; Ashames, Akram; Almas, Uzma; Khan, Shujaat Ali; Yameen, Muhammad Arfat; Nisar, Naveed; Asad, Muhammad Hassham Hassan Bin; Murtaza, Ghulam
Abstract: Purpose of present study was to develop eight formulations of chlorpheniramine (CPM) niosomes according to 2 3 factorial design, characterise on the basis of various evaluation tests, i.e. in vitro drug release, SEM, FTIR, TGA and release kinetics, optimise the eight formulation on the basis in vitro drug release data, formulate gel of optimised dispersion, and to perform in vivo and histopathological study using gel of optimised dispersion on rabbits. Here, N3 having low level of cholesterol and span-80 but high level of span-60(0.1:0.2:0.05) was selected as optimised dispersion of niosomes that showed highest drug release i.e. 88.25% at pH 6 over 24 h of study and followed Korsmeyers-Peppas release kinetics with Fickian diffusion mechanism. After application of statistic by Analysis of variance (ANOVA) with 3D surface plots construction, gel of optimised dispersion of CPM niosomes was formulated, and evaluated by tests for i.e. viscosity, Spreadability, Extrudibility, drug content, drug entrapment, stability, SEM, FTIR, TGA, in vitro drug release, in vivo drug release following first order kinetics and histopathological study. Niosomal gel of CPM ensured successful development using suitable combination of non-ionic surfactants, and effective loading of drug for targeted delivery of drug.